Imaging of OA – From disease modification to clinical utility. Issue 6 (December 2020) - Hayashi, Daichi; Roemer, Frank W.; Eckstein, Felix; Samuels, Jonathan; Guermazi, Ali
Abstract: Multiple disease-modifying osteoarthritis drug (DMOAD) trials were done in the last two decades, but no pharmacological agent has yet been approved by regulatory agencies as an effective therapy to date. Given the fact that we have seen the recent discontinuation of several late-stage drug development trials, a careful strategy is needed in formulating a plan for a successful DMOAD trial – including the various roles of imaging. This narrative review article will summarize how imaging is utilized in osteoarthritis from the perspective of disease modification to clinical utility. We will describe how semi-quantitative and quantitative magnetic resonance imaging approaches have been deployed in DMOAD trials. We will then review the utility of musculoskeletal ultrasound in research and clinical settings. Finally, novel hybrid positron emission tomography/MRI techniques and current research using artificial intelligence will be discussed, focusing on original research. Older publications are included for the discussion of the previous DMOAD trials and other relevant topics where deemed appropriate.